Byssinosis and lung health among cotton textile workers: baseline findings of the MultiTex trial in Karachi, Pakistan. Issue 3 (30th January 2023) - Nafees, Asaad Ahmed; Muneer, Muhammad Zia; Irfan, Muhammad; Kadir, Muhammad Masood; Semple, Sean; De Matteis, Sara; Burney, Peter; Cullinan, Paul
Abstract : Objectives: To assess the association of exposure in cotton mills in Karachi with different definitions of byssinosis and lung health. Methods: This cross-sectional survey took place between June 2019 and October 2020 among 2031 workers across 38 spinning and weaving mills in Karachi. Data collection involved questionnaire-based interviews, spirometry and measurements of personal exposure to inhalable dust. Byssinosis was defined using both WHO symptoms-based (work-related chest tightness), and Schilling's criteria (symptoms with decreased forced expiratory volume in 1 s (FEV1 ). Values of FEV1 /forced vital capacity ratio below the lower limit of normality on postbronchodilator test were considered as 'chronic airflow obstruction' (CAO). Results: 56% of participants had at least one respiratory symptom, while 43% had shortness of breath (grade 1). Prevalence of byssinosis according to WHO criteria was 3%, it was 4% according to Schilling's criteria, and likewise for CAO. We found low inhalable dust exposures (geometric mean: 610 µg/m 3 ). Cigarette smoking (≥3.5 pack-years), increasing duration of employment in the textile industry and work in the spinning section were important factors found to be associated with several respiratory outcomes. Conclusion: We found a high prevalence of respiratory symptoms but a low prevalence of byssinosis. Most respiratory outcomes were associated with duration of employment in textile industry. We have discussed the challenges faced in using current, standard guidelines for identifying byssinosis.